THE INFLUENCE OF AUDIT COMMITTEE CHARACTERISTICS ON COMPANY PERFORMANCE IN SHARIA GENERAL BANKING - Intan Nia Maulida; Srihadi Winarningsih (Universitas Pakuan, 2020)
The research is focused on how characteristics of audit committee affect the company performance. The audit committee characteristics as independent variable is measured by audit committee size, independence of audit commitee, and audit committee meeting frequeny, as the dependent variable, the company performance is measured by return on assets ratio (ROA). To analyze the data this research is using descriptive statistic analysis, the method to test the hypothesis is using multiple linear regression. By several category that applied using purposive sampling, the research is using eleven sharia general banks in Indonesia. The study results shown that the audit committee size and audit committee meetings frequency affected company performance. Then the independence of audit committee has no influence to company performance. Simultaneously, audit committee characteristhics are statistically affected the company performance. Based on this research the company is expected to pay more attention to aspects - aspects that can support return on assets, company management should improve the performance of the audit committee in maximizing the rate of return on assets. This means this study can drawn an implication that the greater size of the audit committee can improve the performance of the audit committee in an effective oversight function in maintaining company performance.